1972
DOI: 10.1161/01.cir.46.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Time Intervals as Measures of the Contractile State of the Left Ventricular Myocardium in Man

Abstract: SUMMARYPrevious studies relating systolic time intervals and measures of cardiac performance have suggested that the time intervals may be useful indices of myocardial contractility. To explore this possibility, systolic times and left ventricular (LV) performance and contractility were measured nearly simultaneously in 14 normal subjects and 56 patients with cardiac disease. Preejection period (PEP) and the ratio of PEP to LV ejection time (LVET) changed significantly with acute inotropic influences (exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
1
12

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(74 citation statements)
references
References 49 publications
6
54
1
12
Order By: Relevance
“…Observations on the relationship between systolic time intervals and direct measures of left ventricular performance, assessed angiographically, have revealed a correlation between LVET, PEP, ICT, and the end diastolic volume and the ejection fraction (2, 16), but it w,as concluded that, "ICT is the interval most intimately related to contractility" (2). The measure of ICT and the determination of the ratio of ICT to LVET appear to be the best indices for predicting a left ventricular contractility and for detecting contractile deficits which may exist in the absence of clear clinical symptoms (2,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations on the relationship between systolic time intervals and direct measures of left ventricular performance, assessed angiographically, have revealed a correlation between LVET, PEP, ICT, and the end diastolic volume and the ejection fraction (2, 16), but it w,as concluded that, "ICT is the interval most intimately related to contractility" (2). The measure of ICT and the determination of the ratio of ICT to LVET appear to be the best indices for predicting a left ventricular contractility and for detecting contractile deficits which may exist in the absence of clear clinical symptoms (2,27).…”
Section: Discussionmentioning
confidence: 99%
“…Two simple composites of systolic time intervals, the ratio of PEP to LVET and the ratio of ICT to LVET, have correlated with ejection fraction and with end diastolic volume in pa-jerk reflex of more than 380 ms (8,13). Excluding workers with these clinical symptoms should have eliminated any factor capable of affecting systolic time intervals (2,7,12,13,21), and therefore any systolic time interval changes found should be caused by exposure to C8 2 • Twenty-two metal arc welding workers, whose ages ranged from 42 to 61 years (mean 56 years), were selected from a machine factory for the reference group. They had never been exposed to C8 2 • With Weissler's method (36,37) the duration of the phases of the left ventricular systole was measured from the simultaneous recording of the ECG, the phonocardiogram, and the carotid and femoral arterial pulse tracings with a Mingograph 81 (Elema 8choenander) recorder at a paper speed of 100 mmls ( fig.…”
Section: Work Sitementioning
confidence: 99%
“…It has been demonstrated that the PEP is associated with cardiac contractility and reflects beta-adrenergic cardiac sympathetic activity (Ahmed, Levinson, Schwartz, & Ettinger, 1972;Cacioppo, Berntson, Binkley, Quigley, Uchino, & Fieldstone, 1994).…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…Thus, it represents the electromechanical delay from the initiation to the action of the heart beat. Changes in cardiac contractility are well established as primarily mediated by the adrenergic signal to the heart (Ahmed et al 1972;de Champlain et al 1980;Harris et al 1967). It is unknown how water consumption level will variously modify the expected changes in SNS outflow as measured by PEP, and how water consumption vs. food will interact to modify HRV.…”
mentioning
confidence: 99%